Penerapan User-Centered Design dalam Perancangan Antarmuka Aplikasi Bengkel Motor Berbasis Mobile - Alif Putra Hermawan; Kurniawan Dwi Irianto (Journal of Information System Research (JOSH), 2025)
The digital transformation in the automotive sector has encouraged motorcycle repair shops to adopt application-based services in order to improve operational efficiency and customer convenience. However, many of the applications developed have not sufficiently considered user needs and experiences, resulting in low adoption rates and user satisfaction. This study aims to design a mobile-based motorcycle repair shop application interface that focuses on user needs and comfort, thereby enhancing the overall user experience. To achieve this goal, the study employs the User-Centered Design (UCD) approach, which actively involves users at every stage of the design process—from needs identification, user persona development, and prototyping using Figma, to design evaluation using the System Usability Scale (SUS) method. The usability test results show that the designed interface achieved an average SUS score of 86.53, which falls into the "Excellent" category, indicating a high level of usability. These findings demonstrate that the application of UCD significantly improves user interaction quality and serves as an effective strategy in the development of digital services for motorcycle repair businesses.